Enrichment of redox-sensitive trace metals (U, V, Mo, As) associated with the late Hauterivian Faraoni oceanic anoxic event - Bodin, Stéphane; Godet, Alexis; Matera, Virginie; Steinmann, Philipp; Vermeulen, Jean; Gardin, Silvia; Adatte, Thierry; Coccioni, Rodolfo; Föllmi, Karl B. (My University, 2007)
The Faraoni Level is a short-lived oxygen-deficient event that took place during the latest Hauterivian. In order to improve our understanding of the palaeoenvironmental conditions that occurred during this event, we have analysed the contents of several redox-sensitive trace elements (U, V, Mo, As, Co, Cd, Cu, Zn, Ni, Pb, Cr) from bulk limestone samples of late Hauterivian–early Barremian age from three reference sections. U, V, Mo and As show consistent and significant enrichments during the Faraoni event whereas the other redox-sensitive trace elements analysed here are not systematically enriched. In order to explain this discrepant behaviour, we propose that the Faraoni Level was deposited during a period of anoxic conditions near the sediment–water interface. The distinctive peaks in U, V, Mo and As contents are traceable throughout the three studied sections and represent a good correlation tool which helps to identify the Faraoni Level and its equivalents in the western Tethyan realm and outside of the Tethys. For example, a peak in U contents in upper Hauterivian sediments of the northwestern Pacific realm (ODP leg 185, site 1149) may well be an expression of the Faraoni event in this particular basin.
Keywords: Hauterivian; Barremian; Chemostratigraphy; Western Tethys; Trace metals